Distal Reoperations after Repair of Acute Type A Aortic Dissection—Incidence, Causes and Outcomes - Igor Vendramin; Daniela Piani; Andrea Lechiancole; Sandro Sponga; Daniele Muser; Massimo Imazio; Francesco Onorati; Elisabetta Auci; Uberto Bortolotti; Ugolino Livi (Reviews in Cardiovascular Medicine, 2022)
Background and Aim of the Study: In patients with acute type A aortic dissection (A-AAD) whether initial repair should include also aortic arch replacement is still debated. We aimed to assess if extensive aortic repair prevents from reoperations patients with A-AAD. Methods: Outcomes after distal reoperation following repair of A-AAD (n = 285; 1977 to 2018) were analysed in 22 of 226 who underwent ascending aorta/hemiarch replacement (Group 1R) and 7 of 59 who had ascending aorta/arch replacement (Group 2R). Results: Distal reoperation was more common in Group 1R (n = 22) than in Group 2R (n = 0) (p < 0.001) while thoracic endovascular stenting was more frequent in Group 2R (7 vs 3, p < 0.001). Indications for reoperation were pseudoaneurysm at distal anastomosis (n = 4, 18%) and progression of aortic dissection (n = 18, 82%) in Group 1R. Indication for thoracic endovascular stenting was progressive aortic dissection in 3 patients of Group 1R and in 6 of Group 2R. Second reoperation was required in 2 patients from Group 1R (2%) during a mean follow-up of 5 years. Median follow-up was 4 years in Group 1R and 7 years in Group 2R (p = 0.36). Hospital mortality was 14% in Group 1R and 0% in Group 2R (p = 0.3). Actuarial survival is 68 ± 10%, and 62 ± 11% for Group 1R and 100% for Group 2R at 5 and 10 years (p = 0.076). Conclusions: Distal reoperations after A-AAD repair have an acceptable mortality. An extensive initial repair has lower rate of reoperation and better mid-term survival and should be indicated especially for young patients in experienced centers.